RETRACTED: Smartphone Interventions Effect in Pediatric Subjects on the Day of Surgery: A Meta-Analysis - Li, Li; Ma, Jianping; Ma, Dan; Zhou, Xiaokang (Frontiers in Surgery, 2021)
Background A meta-analysis was performed to evaluate the effect of smartphone interventions on pediatric subjects' anxiety at induction on the day of surgery compared to oral midazolam, or control. Methods A systematic literature search up to June 2021 was performed and 9 studies included 785 pediatric subjects on the day of surgery at the start of the study; 390 of them were using smartphone interventions, 192 were control, and 203 were using oral midazolam. They were reporting relationships between the effects of smartphone interventions on pediatric subjects' anxiety at induction on the day of surgery compared to oral midazolam, or control. The mean difference (MD) with its 95% confidence intervals (CIs) was calculated to assess the effect of smartphone interventions on pediatric subjects' anxiety at induction on the day of surgery compared to oral midazolam, or control using the continuous method with a random or fixed-effect model. Results Smartphone interventions in pediatric subjects were significantly related to lower anxiety at induction on the day of surgery (MD, -19.74; 95% CI, -29.87- -9.61, p<0.001) compared to control, and significantly related to lower anxiety at an induction in the day of surgery (MD, -7.81; 95% CI, -14.49- -1.14, p=0.02) compared to oral midazolam. Conclusions Smartphone interventions in pediatric subjects on the day of surgery may have lower anxiety at induction compared to control and oral midazolam. Furthers studies are required to validate these findings.